If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -3 = -4x + 1 Reorder the terms: -3 + -6x = -4x + 1 Reorder the terms: -3 + -6x = 1 + -4x Solving -3 + -6x = 1 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -3 + -6x + 4x = 1 + -4x + 4x Combine like terms: -6x + 4x = -2x -3 + -2x = 1 + -4x + 4x Combine like terms: -4x + 4x = 0 -3 + -2x = 1 + 0 -3 + -2x = 1 Add '3' to each side of the equation. -3 + 3 + -2x = 1 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = 1 + 3 -2x = 1 + 3 Combine like terms: 1 + 3 = 4 -2x = 4 Divide each side by '-2'. x = -2 Simplifying x = -2
| 5(y+x)=20+3y | | 4x+25=60 | | (-8.2)+(-3.3)= | | f(x)=10x-7 | | -4w-11=4w+21 | | 16+3n+n=52 | | x-3(9)=-4 | | x+3=1.5 | | f(x)-2x+5whenf(x)=75 | | 1.4+1.1=8.3-m | | 5=49-7 | | 4y-3y-4=5 | | -2y-0.1-0.9y-4.6y-5= | | 7x+1=51+2x | | 4y-x=5 | | 3x+3+x=45 | | -22-5x=-77 | | f(x)=6x+15 | | 8=-2x+5+4x | | 3-y=12 | | 8g+7=119 | | 30=-10x-70 | | 7(x-1)=2x+65 | | 15x+5y=175 | | x+19+2x=-12-2x-19 | | -7-x=-1-2x | | -3+x/6=6 | | -77=-22-5x | | 8x-0.33y=16 | | 7(f+2)=8+5f | | X+19+3x=-26-3x-32 | | 2=-3+x/8 |